Reducing truck congestion at ports - classification and trends - Ann-Kathrin Lange; Anne Kathrina Schwientek; Carlos Jahn (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
Truck drayage in container ports faces several challenges. Due to the ongoing growth of container ship sizes, there are increasingly high peak situations in landside container handling at logistic nodes in the port, e.g. container terminals, empty depots, freight stations. In combination with rising demands to improve the port's ecological footprint this requires the port and its companies to adapt to the situation in order to reduce congestion. To identify important methods, key parameters, past developments and future trends a classification scheme based on an extensive literature survey on waiting times at terminals and drayage operations is conducted and applied to 71 publications. The analyzed methods to reduce congestion in the port range from optimizing the infrastructure to controlling truck arrival times. While this problem is mainly analyzed from a container terminal perspective, its impacts also affect other stakeholders in the port as trucking companies, empty depots or freight stations. Past literature surveys mainly focus on either one method or one stakeholder. This led to limited assessments for the whole drayage networks in ports. Therefore, the developed classification scheme is a basis to identify promising further research areas while enabling a more holistic approach.
urn:nbn:de:gbv:830-88217785; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; drayage; port logistics; congestion; classification scheme